Valuable Choices: Prominent Venture Capitalists’ Influence on Startup CEO Replacements - Conti, Annamaria; Graham, Stuart J. H. (Management Science, 2020)
This paper explores how prominent venture capitalists (VCs) affect chief executive officer (CEO) replacement in startups. Defining prominence using eigenvector centrality, we use matching methods and instrumental variables to show that startup CEO replacement occurs more often and faster when prominent VCs participate. We further explore these VCs’ comparative advantage in managing CEO turnover, finding that the prominent VC effects increase as replacement costs rise, such as when incumbent CEOs are entrenched or possess specialized technology know-how, or when startups are in an early stage. When prominent VCs participate, replacement CEOs are disproportionately experienced outsiders—external hires who possess prior startup CEO experience. Our results reveal that CEO turnover is associated with increases in startups’ ex post innovation and survival performance, with experienced outsider CEO replacements showing the strongest survival rates. This paper was accepted by Gustavo Manso, finance.